Penggunaan Artificial Intelligence Animated Drawings Dalam Kegiatan Menggambar Sebagai Upaya Meningkatkan Kreativitas Anak Usia Dini - Pratiwi, Shelly; Zahra, Rahmi Rohimatul (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
This research is motivated by the low level of creativity in drawing activities among early childhood students aged 5–6 years at RA Darul Ihsan Pinggirjati. Based on initial observations, 20% of the children (2 out of 10) were categorized as "not yet developing" (BB), while 80% (8 out of 10) were in the "beginning to develop" (MB) stage. The purpose of this study is to determine the effectiveness of using Artificial Intelligence (AI) Animated Drawings in enhancing the creativity of young children during drawing activities at RA Darul Ihsan Pinggirjati. The study employed a qualitative approach using the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of two cycles. The subjects were 10 children from group B1. Data were collected through direct observation, teacher interviews, and documentation of children’s artworks. The findings show that the use of AI Animated Drawings facilitated children in developing visual ideas by transforming their drawings into interactive animations, thereby enhancing creativity in the aspects of fluency, originality, flexibility, and elaboration. The improvement in creativity was evident in the increase in the percentage of children meeting the success criteria, reaching 90% by the end of cycle II. This study confirms that AI technology is not only engaging for children but also provides stimulation that supports the development of fine motor skills and imagination.